2021
DOI: 10.1002/rth2.12407
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutation in coagulation factor VII (Carmel mutation): Identification and characterization

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
1
0
1
Order By: Relevance
“…Previously published articles revealed that the hemorrhagic diathesis in severely affected compound heterozygotes was variable and did not always correlate with the low FVII activity documented [16]. This was also the case in our patients, presenting as asymptomatic during the perioperative period despite an exclusively dysfunctional FVII in their plasma, suggesting a less link between FVII activities and bleeding tendency (see Table 1).…”
Section: Discussionsupporting
confidence: 66%
“…Previously published articles revealed that the hemorrhagic diathesis in severely affected compound heterozygotes was variable and did not always correlate with the low FVII activity documented [16]. This was also the case in our patients, presenting as asymptomatic during the perioperative period despite an exclusively dysfunctional FVII in their plasma, suggesting a less link between FVII activities and bleeding tendency (see Table 1).…”
Section: Discussionsupporting
confidence: 66%
“…Полиморфизм гена FVII заключается в замене G на А в позиции 10976, что приводит к изменению биохимических свойств F7, в котором происходит замена аминокислоты Arg на Gln в позиции 353. Полиморфизм 10976 G/A FVII приводит к снижению активности и секреции FVII в кровь [25].…”
Section: генunclassified
“…ELISA technique using monoclonal FVII-specific antibodies can also be used to measure the plasma level of the FVII antigen (68). In patients with severe, mild/moderate, and asymptomatic congenital FVII deficiency, the levels of FVII:Ag and FVII:C are widely overlapping and cannot be used to predict the clinical severity of the disease; thus, collecting a detailed family history is essential (51). However, the FVII:Ag and FVII:C assays allow one to distinguish between CRM -(FVII:Ag and FVII:C reduced with the same ratio), CRM + (a decreased FVII:C with normal FVII:Ag), and CRMred (FVII:Ag reduction but not as much as FVII:C) (5,6,69).…”
Section: Diagnosismentioning
confidence: 99%